Book Review: Archaeology as Festival: Virtual Wanderings through FestivalCHAT during Covid-19 by Kiddey and Caraher (eds) - Steve Burrow (EXARC Journal)
Archaeology as Festival reports on the 2020 annual conference of the Contemporary and Historical Archaeology Theory group. It contains fifteen contributions and includes papers reporting on public stairways in Pittsburgh, toilet graffiti in Lisbon, and a kitchen wall in the Netherlands. With case studies like these one might doubt the relevance of the contents to the EXARC community, but there is much more to this fascinating volume than historical record, and its importance here, stems less from the detail of the subject matter and more from the circumstances in which it was produced.